2022
DOI: 10.3389/fped.2022.774973
|View full text |Cite
|
Sign up to set email alerts
|

Application of Allogeneic Human Acellular Dermal Matrix Reduces the Incidence of Fistula in Hypospadias Repair

Abstract: BackgroundUrethrocutaneous fistula is one of the most common complications arising from hypospadias surgery. The purpose of our study was to investigate the effectiveness and safety of allogeneic human acellular dermal matrix (HADM) application as a means of preventing the occurrence of urethrocutaneous fistula following hypospadias surgery.MethodsThis is a non-randomized study of 219 cases (out of 270 patients with hypospadias) which satisfied inclusion and exclusion criteria. These patients were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…AlloDerm is well established and widely recognized in the field of reconstructive surgery. It was selected as a control material in this study because it is clinically relevant and its value for urethral reconstruction is well documented [47][48][49]. Morphological assessment of the CPC scaffolds revealed a nano/microfibrous structure, which was supportive of cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…AlloDerm is well established and widely recognized in the field of reconstructive surgery. It was selected as a control material in this study because it is clinically relevant and its value for urethral reconstruction is well documented [47][48][49]. Morphological assessment of the CPC scaffolds revealed a nano/microfibrous structure, which was supportive of cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicates that the utilization of ADM derived from bovine skin as a coverage material for proximal hypospadias repair can effectively decrease the occurrence of urinary fistula formation (89). Wu et al (91) investigated the use of ADM in hypospadias repair and demonstrated a significant reduction in urinary fistula complications without an increased risk of infection and urethral stricture. Given the detrimental effects of urine on the cellular components of tissue-engineered urethra, it is crucial for the scaffold to possess sufficient impermeability as an isolation barrier.…”
Section: Using Cell-seeded Adm Scaffold Materialsmentioning
confidence: 99%